STUDY OF POSTURAL SAFETY AND MUSCLE ACTIVITY ANALYSIS FOR DEADLIFT EXERCISE IN GYM - Mohd Azrin, Mohd Said; Kong, Jing Hui; Nor Kamaliana, Khamis (2022)
In exercise or workouts, postural safety and ergonomics are some of the factors that need to look into for the safety of humans or athletes. Good postural safety of an athlete can reduce accidents and injury. The lack of postural safety and ergonomic features could result in negative effects, especially on athletes' physical and mental health. To evaluate the posture problem due to comfortability and ergonomics, a survey has been conducted. This was implemented by distributing questionnaires sheets for athletes to find out their experience and opinions regarding uncomfortable feelings and injuries. Ergonomic and injury problems commonly arise due to bad posture. The purpose of this study is to determine the postural safety problems and risk assessment while deadlifting among student-athlete in the gym. It also to study the back muscle activity analysis for three types of position and best angle while deadlifting. The surface electromyography (EMG), Kinovea software and Matlab software were used in this research to assess potential risk areas that occur during deadlifting. This study shows that deadlift in posture can be improved by ensuring the back and shoulder posture is in the proper position. The result shows that the deadlift position of straight shape of leg position with 105o angle is the less time to complete the exercise with less muscle activity for 10 repetitions. Therefore, further study on different deadlift exercises can be done in the future to indicate the postural safety of an athlete.